2019
DOI: 10.21203/rs.2.10497/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The items in the Chinese version of the Montreal Cognitive Assessment Basic discriminate among different severities of Alzheimer’s disease

Abstract: Background To determine whether items of the Chinese version of the Montreal Cognitive Assessment Basic (MoCA-BC) could discriminate among cognitively normal controls (NC), and those with mild cognitive impairment (MCI), mild Alzheimer’s disease (AD), and moderate-severe (AD), as well as their sensitivity and specificity.Methods MCI (n=456), mild AD (n=502) and moderate-severe AD (n=102) patients were recruited from the memory clinic, Huashan Hospital, Shanghai, China. NC (n=329) were recruited from health c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…In contrast, the part B subset of the Trail Making test was correctly performed by only 37% of people with an elementary-level education, and <30% of individuals with an elementary-level education and 7% of illiterate individuals correctly completed cube drawing (Gómez et al, 2013 ). Similarly, studies using MoCA in populations of Brazilian (Apolinario et al, 2018 ), Turkish (Yancar and Öscan, 2015 ), and Chinese (Zhang et al, 2019 ) origin have reported the influence of education level on MoCA cut-off points. A systematic review on the cultural validity of MoCA (O'Driscoll and Shaikh, 2017 ) and a critical review on BCS for older adults with low levels of education (Tavares-Júnior et al, 2019 ) suggest different cut-off points of MoCA according to education level.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, the part B subset of the Trail Making test was correctly performed by only 37% of people with an elementary-level education, and <30% of individuals with an elementary-level education and 7% of illiterate individuals correctly completed cube drawing (Gómez et al, 2013 ). Similarly, studies using MoCA in populations of Brazilian (Apolinario et al, 2018 ), Turkish (Yancar and Öscan, 2015 ), and Chinese (Zhang et al, 2019 ) origin have reported the influence of education level on MoCA cut-off points. A systematic review on the cultural validity of MoCA (O'Driscoll and Shaikh, 2017 ) and a critical review on BCS for older adults with low levels of education (Tavares-Júnior et al, 2019 ) suggest different cut-off points of MoCA according to education level.…”
Section: Discussionmentioning
confidence: 91%
“…The neuropsychological tests were all designed by the Hong Kong University and Anhui Medical University [25], except MoCA. The Beijing Version of the Montreal Cognitive Assessment Test (MoCA) was administered to assess global cognitive function [26]. An adjusted MoCA score < 26 was considered cognitive impairment.…”
Section: Neuropsychological Backgroundmentioning
confidence: 99%
“…Unfortunately, only 86% cases could be correctly identified as either normal or MCI [7]. Recent studies in mainland China suggested that the cutoffs for MCI were 24 in a clinical sample [8] and ranged from 18 to 25 in normative samples [9][10][11]. ese studies suggested that the cutoffs were contingent upon sampling (i.e., normative versus clinical), age, education, cultural background, and validating criteria [12].…”
Section: Introductionmentioning
confidence: 99%